ELLIPSIS AND SUBSTITUTION IN RIDWAN KAMIL CONVERSATION ON INTERVIEW: HIS EXCELLENCY RIDWAN KAMIL ON URBAN MOBILITY PROJECT - Ismy Nurazizah; Iman Santoso (PROJECT (Professional Journal of English Education), 2020)
This research aims to find out the use of ellipsis and substitution in Ridwan Kamil’s conversation on interview. There are three types of ellipsis, namely nominal ellipsis, clausal ellipsis and verbal ellipsis. While, substitution has three types, there are nominal substitution, verbal substitution and clausal substitution as cited by Halliday (2014). The method used in this research is quantitative and qualitative method. To collect the data, the writers used several steps. First, downloading the video in internet. Second, transcript the dialogues into the texts. Third, reading the conversation texts. After that, identifying the sentences of Ridwan Kamil’s conversation. Then, counting the sentences which includes to ellipsis and substitution. And the last, describing the reason why the sentences includes ellipsis and substitution. From the data, the writers found seven sentences are defined as an ellipsis and substitution. One sentence as a nominal ellipsis, one sentence as a clausal ellipsis, and verbal ellipsis was not found in the data. Five sentences included as a substitution. Two sentences defined as a nominal substitution, one sentence included as a verbal substitution and two sentences as a clausal substitution.